ANALISIS PARAMETER MESIN LASER TUBE CUTTING TERHADAP SURFACE ROUGHNESS PADA SQUARE PIPE ST 37 MENGGUNAKAN TAGUCHI METHOD - Rachman, Farizi; Wardani, Lintang Aditya; Sidi, Pranoto; Setiawan, Tri Andi; Hamzah, Fais; Maulana, Danis (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Parameter optimization is a technique used in the manufacturing process to create products with optimal quality. The research aims to find the optimal settings in the laser tube cutting machine so that the surface of the square pipe ST 37 becomes smoother and flatter. The settings to be changed are laser focal point, gas pressure, nozzle distance and laser power. This research uses Taguchi method with L9 (34) orthogonal matrix to analyze the experimental results. With each parameter having 3 levels according to the orthogonal matrix, the experiment was conducted 9 times with 3 replications to make the results more valid. In the research results obtained the most optimal combination of parameters on the laser tube cutting machine on the response of the cutting rate is with a combination of focus point parameters at level 1 of 0 mm, gas pressure at level 1 of 0.6 bar, and laser power parameters at level 1 of 1800 W.